Validation of FoodChek™ - Salmonella for Rapid Detection of Salmonella in Eggs, Derivative Products, and the Environment. (27th November 2019) - Buzinhani, Melissa; Tremblay, Renaud; Martinez, Gabriela; Giuffre, Michael; Hammack, Thomas; Fernandez, Maria Cristina; Ziemer, Wayne
Abstract: The FoodChek™ - Salmonella assay is an immunomagnetic lateral flow assay for the rapid detection (shorter than 24 h) of the most frequently isolated Salmonella (groups B–E) in eggs, egg-derivative products, and environmental surfaces. The FoodChek - Salmonella assay correctly identified 99.6% (239/240) of the samples tested in the matrix studied, and the statistical analysis of the method comparison study results demonstrated that it performs as well as U.S. culture-based reference methods. Ninety-nine percent of the 103 Salmonella strains tested belonging to serogroups B–E were detected during the inclusivity study. Concerning the exclusivity, 31 nontarget strains were tested. No cross-reactivity was observed in FoodChek - Salmonella assay enrichment conditions. In addition, the assay shows strong robustness, good stability, and consistency among lots. The present study proves that the assay is an effective tool for the rapid detection of Salmonella spp. in whole liquid eggs, liquid egg white (liquid egg albumen), shell eggs, dried whole eggs, dried egg yolks, and environmental surfaces as stainless steel, plastic, rubber, ceramic tiles, and sealed concrete.